Analisis Kepemimpinan Kristus serta Implikasinya terhadap Kepemimpinan pada Gereja Masa Kini - Wakkary, Adrian MF; Wungouw, Jefri (Sekolah Tinggi Teologi Anugrah Indonesia, 2025)
Christian leadership is often equated with secular leadership, potentially deviating from God's intended purpose. This research aims to analyze the concept of Christ's leadership from a biblical perspective, focusing on understanding leadership as a divine calling through a comprehensive study of the four Gospels. The research employs a qualitative methodology with a literature study approach, utilizing data sources from journals, books, and observations of church leadership practices. Research findings reveal that authentic Christian leadership is a manifestation of divine calling to serve, rather than merely human effort. Such leadership is characterized by total dedication to the mission of proclaiming God's truth among His people. The study concludes that Christian leadership is fundamentally a spiritual responsibility determined by God's sovereignty, transcending organizational positions or human ambitions.